ISOLATION AND IN-VITRO HYDROLYSIS OF GLOBULIN G1 FROM LENTILS (LENS-CULINARIS, MEDIK) - Neves, Valdir Augusto [UNESP]; Lourenco, E. J. (Food Nutrition Press Inc, 1995)
The major globulin fraction from lentil seeds was investigated with respect td in vitro hydrolysis by trypsin and chymotrypsin. Globulin was isolated by a NaCl-ascorbate extraction procedure and purified by DEAE-cellulose chromatography and gelfiltration chromatography on Sepharose CL-6B. The purity and identification of the protein were performed by PAGE. The native globulin, with a molecular weight of 375 kD, was resolved by SDS-PAGE into twelve polypeptides with molecular weights ranging from 61 to 14.5 kD. Native and heated globulin GI was hydrolyzed with trypsin and chymotrypsin. SDS-PAGE indicated that native globulin was more resistant to digestion than heated protein. Amino acid analysis of the major globulin revealed that glutamic acid was present in the largest concentration, followed by aspartic acid, arginine and leucine. As is also the case for other legumin-like globulins, lentil GI was deficient in sulfur-containing amino acids.